The Patriotic Attitudes of the Prospective Teachers - Melike Faiz (International Journal of Psychology and Educational Studies, 2020)
The concept of patriotism can be defined as loving the homeland and making sacrifices for it. From this perspective, it can be said that the concept of patriotism has a function of uniting and integrating the people who live on the same land and gives people an understanding which is proud of its history. Patriotism is also a dynamic concept. Because it is the behavior, consciousness and understanding that we put forward in every moment of life, in every field and in all our actions. It is also the basic condition of being a good and effective citizen. With the impact of globalization and technology, while the world is rapidly becoming a big village, civil wars, migrations, economic crises, hunger, famine and confusion in various continents and countries of the world increase the need for protection of national values and reveal the importance of patriotic education. On the other hand, patriotic education is aimed to be provided to the students who will be the citizens of the future through the education programs in the schools. For this reason, determining the patriotism attitudes of the teachers who will gain the patriotism value to the students is important in determining the deficiencies and taking measures in the acquisition of this value. In this context, the aim of the study was to reveal the pre-service teachers' patriotic attitudes. In the research, screening model which is one of the quantitative research types was used. The study group of the research is composed of Social Studies, Turkish, Science, Mathematics, Primary School and Preschool teachers who are studying in the 3rd and 4th grades of a state university in the fall semester of 2019-2020 academic year. The sample type of the study was determined as purposeful sample. In the study, “Attitude Scale of Patriotism Attitude” which was developed by Schatz, Staub and Lavine (1999) and adapted into Turkish by Yazıcı (2009) was used. As a result, according to the gender of male teachers were more patriotic than famela students. According to the department variable, there is a difference between the department of social studies education and preschool education in the blind patriotism and whole scale scores, in favor of social studies education. There was no significant difference according to family income and class level.